Applicability of different isothermal EOS at nanomaterials - Joshi, Deepika P. (2013)
The present study explains the behaviour of nanomaterials such as AlN, CdSe, Ge, WC, and Ni- and Fe-filled-MWCNTs under high pressure. Among the number of isothermal EOSs available, we prefer only two parameter-based isothermal equations (i.e., Murnaghan equation, usual Tait's equation, Suzuki equation and Shanker equation). The present work shows the theoretical study of thermo-elastic properties especially relative compression (V/V0), isothermal bulk modulus (Kp/K0), and compressibility (αP)/α(0)) of nanomaterials. After comparing all formulations with available experimental data, we conclude that pressure dependence of relative compression (V/V0) for the nanomaterials, are in good agreement for all the equations at lower pressure range. At higher pressure range, Suzuki and Shanker formulations show some deviation from experimental values.